Transforming history through digitization and 3D heritage replication - Themistocleous, Kyriacos (My University, 2025)
The transformative potential of digitization and 3D heritage replication provides a compelling methodology for preserving and enhancing accessibility to cultural heritage. Through detailed 3D digitization and accurate 3D printing, tangible antiquities can be effectively duplicated, significantly extending their reach for research, education, and public engagement. Utilising advanced technologies such as 3D photogrammetry and laser scanning, the digitisation process accurately captures the physical attributes of cultural artefacts and secures their digital preservation for future generations. This practice ensures that historical objects vulnerable to deterioration or destruction due to environmental factors or human activity remain accessible indefinitely. Benefits of digitizing and replicating cultural heritage objects include enhanced preservation, wider dissemination, and increased accessibility. Digital models can be shared globally, providing invaluable resources for research and education without risking damage to original artefacts. Furthermore, 3D printed replicas offer tangible, sensory experiences, significantly enriching public engagement by allowing individuals to interact physically with historical items. Societally, the widespread adoption of 3D digitization and heritage replication contributes to the democratization of culture, breaking geographical and socio-economic barriers that traditionally limit access to historical artefacts. Educational institutions and communities can benefit from virtual museums and interactive learning resources, promoting cultural awareness and heritage appreciation among diverse populations. Additionally, this digital shift fosters innovation in cultural tourism and creative industries, supporting economic development and cultural sustainability. This approach not only preserves but actively enhances the cultural value and understanding of heritage objects, making history accessible and relevant in unprecedented ways.
Keywords: Digitization; Transforming history